State recognition of traditional authority in Mozambique: The legible space between state and community - Lars Buur; Helene Maria Kyed (Danish Institute for International Studies (DIIS), 2006)
In 2000 the Mozambican government initiated a process of formally recognizing traditional leaders both as representatives of local community interests and as assistants of local state organs. Twenty-five years after the FRELIMO government abolished the formal power of traditional leaders, the Decree 15/2000 provided for their re-inclusion in the performance of a long list of state administrative tasks and re-named chiefs or régulos as `community authorities'. In line with post-war commitments to democratic decentralization, the Decree promises to enhance community participation in local administration and rural development. The role of traditional authority as intermediary between rural populations and the state is not a new problematique, but has been part of the ongoing process of state formation from Portuguese colonial rule, through post-colonial FRELIMO nation-state building, to today's liberal democratic governance. This article addresses some fundamental questions pertaining to the official recognition of traditional leaders as community authorities. It argues that the double role that they are expected to fulfil as both community-representatives and state-assistants is not equally balanced either in the Decree 15/2000 or in its implementation: the scale tips heavily towards the state-assistance role. After a brief history of traditional authority as a basis for understanding the recent official recognition, the article outlines the main techniques through which traditional leaders have been made legible as `true' community representatives capable of working as state assistants. Based on analysis of the processes of legibility, the article scrutinizes the reified notions underpinning the Decree, such as the understanding of `traditional rules' and the definition of `community'. It concludes by pointing out some consequences of these reified notions for kin-based forms of community authority.
Keywords: 330; Regierung; Regionalverwaltung; Verwaltungsreform; Politiker; Mosambik